COMPARATIVE PHYTOCHEMICAL ANALYSIS OF PHLOGACANTHUS THYRSIFLORUS NEES: IMPLICATIONS ON ATTENUATION OF PRO-OXIDANTS AND PATHOGEN VIRULENCE IN CAENORHABDITIS ELEGANS MODEL SYSTEM - Suchiang, Kitlangki; NITASHA HIMANSHU KAYDE (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Phlogacanthus thyrsiflorus Nees of Acanthaceae family is endogenous to sub-tropical Himalayas. It has been reported to be used traditionally in Jaintia tribe of Meghalaya, India, for the treatment of many ailments. The aim was to detect the active compounds present in the leaves and evaluation of its in vitro free radicals scavenging potential. Leaves protective effects in vivo will be investigated using Caenorhabditis elegans modelÂ system utilizing wild type and mutant strains and the phenomena of host-pathogen interactions. Methods: Gas chromatography-mass spectrometry was used for detection of different compounds present. The versatility of leaf extracts to scavenge different free radicals generated in vitro was assessed with different in vitro methods. Survival analysis of wild type and mutant strains C. elegans under enhanced pro-oxidants exposure was investigated in vivo. The fast killing assay was also performed to study the extracts modulatory activities on host C. elegans survival under pathogen Pseudomonas aeruginosa infection. Results: About 40 compounds were detected in methanolic fraction of the extract with variable percentages. Both aqueous and methanol extract possessed remarkable, versatile free radical scavenging activity irrespective of the types of free radical generated. The in vivo experiments are in compliance with observable increased survival ability percentage of C. elegans under intense exogenous oxidative stress and pathogen infection. Conclusion: Our findings enlightened the different bioactive compounds present with versatility of P. thyrsiflorus in tackling different free radicals generated both in vitro and in vivo that highly support for its candidature as a good antioxidant source. Our findings may justify the historical relevance of this plant in herbal remedies that could form the basis for inquiry of new active principles.